Approach to automation of a process of yeast inoculum production on industrial scale for ethanol production - Ordóñez-Ortega, Ibeth Viviana; Rivera-Mariño, Iber; Franco-Mejía, Edinson (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2013)
The results of an applied research for automation the stage of reproduction of Saccharomyces cerevisiae yeas to produce ethanol, are presented in this paper. The identification of the variables to be instrumented, the instrumentation requirements and the proposed control scheme are based on the analysis of the functioning and operation of the process.